Characteristics of Soil Degradation as Affected by Long-term Land Use and Management Systems in a Semi-arid Sandy Soil in North China - Su, Yougzhong; Zhazo, Halin (Annals of Arid Zone, 2016)
The conversion of natural grassland to cropland had resulted in severe deterioration. in soi I resource and rapid expansion of land desertification in the semi-arid agro-pastoral zone of north China. To assess the effects of land-use change and subsequent soil and crop management practices on soil degradation in semi-arid Horqin Sandy Land. north China. soils were sampled from adjacent natural grassland (NG) and cultivated land (converted from NG in 1986). including hawthorn (Crataegus sanguinea L.) orchard (HO), monocultured cropland (MC) and alley-cropping land (interpolating with plum trees and crops) (AC). Land use change and subsequent tillage practices resulted in significant decreases in silt content, water-holding capacity, dry macro-aggregate, organic C. total N, basal soil respiration, and phosphatase activities. However, contents of total and available P were improved by application. of phosphorus fertilizers in cultivated systems. Compared with NG soil, the extent of soil degradation in the cultivated system was ranked in the order: the conventional tilled cropland (MC) > the tilled alley-cropping system (AC) > the HO pattern with minimized disturbance. From perspective of soil resource and environment conservation, a viable option for protecting soil resources and achieving sustainable land use should be to stop conversion of grassland to cropland and to translate the conventional tillage into conservation tillage.